2015
DOI: 10.1038/srep13027
|View full text |Cite
|
Sign up to set email alerts
|

Improve oxidation resistance at high temperature by nanocrystalline surface layer

Abstract: 9% Cr martensitic heat resistant steels such as P91 steel have been considered as the primary candidate structural materials for advanced fossil fired power plants and generation IV nuclear power plants. Due to long-term exposures to high temperatures, the high temperature creep resistance and high temperature oxidation resistance of P91 steel should be simultaneously improved. A Cr content of around 9 wt% in martensitic heat resistant steels is required for the optimization in creep properties, and creep resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The enhancement of anti-oxidation properties in FeCoCr was due to the existence of Co and Cr; the former is more difficult to oxidize than the Fe element [54], while the latter can form a dense protection layer for Fe elements [55]. From thermogravimetry results, the FeCoCr powders are expected to stay stable at 300 After the proper modulation of permittivity, the reflection loss (RL) of the FeCoCr powders was calculated and discussed.…”
Section: Resultsmentioning
confidence: 99%
“…The enhancement of anti-oxidation properties in FeCoCr was due to the existence of Co and Cr; the former is more difficult to oxidize than the Fe element [54], while the latter can form a dense protection layer for Fe elements [55]. From thermogravimetry results, the FeCoCr powders are expected to stay stable at 300 After the proper modulation of permittivity, the reflection loss (RL) of the FeCoCr powders was calculated and discussed.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive research over almost 40 years resulted in the development of commercial steels like X20, TAF 650, T/P91, T/P92 and T/P93. However, the high-temperature resistance of all these steels is based on traditional metallurgical concepts such as solid solution, precipitation, and dislocation hardening [121][122][123]. Indeed, recent efforts are focused on increasing the high-temperature resistance by controlling the precipitation kinetics of nitride and intermetallic phases.…”
Section: ( )mentioning
confidence: 99%
“…Additionally, the 1000_15 min CrSi 2 sample has the lowest crystallite size. It was reported that materials with nanocrystalline size affect thermal stability [57][58][59][60]. Birbilis et al [59] showed that nanocrystalline materials with fine grain size and high diffusion coefficients facilitate the formation of protective oxides.…”
Section: Siliconizing Stepmentioning
confidence: 99%